THE EXPANSION OF JEPARA IN THE XVI CENTURY AND ITS POTENTIAL AS A SUPPLEMENT TO HISTORY LEARNING MATERIALS - Hana, Muhammad Yusril; Wijaya, Daya Negri (Universitas Negeri Yogyakarta, 2024)
This research aims to develop a history learning supplement on the XVI Century Jepara Expansion. This article is made using historical research methods, in the form of topic selection, source collection or heuristics in the form of